A dual band spin-selective transmission metasurface and its wavefront manipulation. Issue 24 (15th June 2021) - Yue, Zhen; Zheng, Chenglong; Li, Jie; Li, Jitao; Liu, Jingyu; Wang, Guocui; Chen, Mingyang; Xu, Hang; Tan, Qi; Zhang, Haijian; Zhang, Yating; Zhang, Yan; et al.
Abstract : A spin-selective focusing metasurface composed of chiral meta-atoms. Abstract : Chiral metasurfaces which can achieve different optical responses for left-handed and right-handed circularly polarized (CP) light have been proposed. Most of the research studies on chiral metasurfaces focus on improving circular dichroism (CD) and realizing dynamic manipulation of the chiro-optical response. However, there have only been a few reports on the multi-band chiro-optical response. Here, we propose an all-silicon chiral meta-atom which can realize spin-selective transmission in a dual band. In addition, a terahertz metasurface with spin-selective transmission through phase arrangement is designed by using chiral meta-atoms satisfying a gradient geometric phase. Under left-hand circularly polarized (LCP) incidence, the metasurface generates a focused right-hand circularly polarized (RCP) beam which is focused at a distance of 4.8 mm from the exit surface of the metasurface. Our work broadens the concept of metasurface design and may attract more researchers' attention on the applications of chiral metasurfaces.